2011
DOI: 10.1002/app.33919
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface‐modified zinc oxide as cure activator on the properties of a rubber compound based on NR/SBR

Abstract: Zinc oxide (ZnO) and nano-zinc oxide (nZnO) were surface modified by polyethylene glycol (PEG) and poly propylene glycol (PPG). Modification of particles were controlled by transmission electron microscopy, Brunauer, Emmett, Teller specific surface area measurement, infrared (IR) spectroscopy, and differential scanning calorimetry. IR spectra were shown that the interactions between surface modifiers and particles are hydrogen bonding. Modified particles were applied as an activator in vulcanization of natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Environmental protection agency has classified ZnO as hazardous chemical for the environment and has suggested that its application in rubber compounds should be reduced . To solve this environmental problem, very recently several studies have been made by different researchers for the reduction of ZnO level in rubber vulcanization by introducing nano ZnO as cure activator. Sahoo and Bhowmick reported that nano ZnO is much more effective curing agent for carboxylated nitrile rubber (XNBR) in comparison to conventional ZnO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental protection agency has classified ZnO as hazardous chemical for the environment and has suggested that its application in rubber compounds should be reduced . To solve this environmental problem, very recently several studies have been made by different researchers for the reduction of ZnO level in rubber vulcanization by introducing nano ZnO as cure activator. Sahoo and Bhowmick reported that nano ZnO is much more effective curing agent for carboxylated nitrile rubber (XNBR) in comparison to conventional ZnO.…”
Section: Introductionmentioning
confidence: 99%
“…Panampilly and Thomas investigated the suitability of nano ZnO as cure activator in the sulfur vulcanization of NR. In another work, Taghvaei‐Ganjali et al . used surface‐modified nano ZnO to enhance the physico‐mechanical properties of rubber compounds.…”
Section: Introductionmentioning
confidence: 99%
“…According to published data on vulcanisation dynamics, during active complex formation the divalent metal ions act as a Lewis acid and the accelerator acts as a Lewis base. The acidic properties of a metal ion also depend upon its size and charge, according to the following equation: [10] Cation acidity ¼ K:…”
Section: Resultsmentioning
confidence: 99%
“…This latter effect may be due to the adsorption of metal ions on the surface of the rubber particles. [7] Recent studies of the effects of various concentrations (10,20, 30 ppm) of metal ions such as Fe 2þ and Mn 2þ upon the physico-mechanical properties of radiation-vulcanised natural rubber latex (RVNRL) [8] report that tensile strength and tear strength of the irradiated films increased with increasing metal ion concentration as well as radiation dose. However, since the effects of divalent metal ions upon the curing characteristics and dynamic mechanical properties of NR have not as yet been reported, the aim of this research was therefore to investigate the effects of divalent metal ions such as Cu 2þ , Fe 2þ and Ca 2þ upon these important properties of NR.…”
Section: Introductionmentioning
confidence: 99%
“…Nano-ZnO is a more efficient activator compared with conventional micro-ZnO reducing the vulcanization time of sulphur cured rubber, due to increased surface area [2], [3]. Before blending nano-ZnO into rubber, surface modification of nano-ZnO is usually applied to enhance the interfacial interaction between nanoparticles and rubber matrix, and therefore leading to better dispersion of the nanoparticles [4], [5], [6]. In our study, the selected nitrile rubber (NBR) compound which contained silane modified nano-ZnO was cured on a polyamide 6 (PA6) substrate.…”
Section: Introductionmentioning
confidence: 99%